Wind Transformation around Residential Buildings in Street Canyons. (2016) - Balakin, V.V.; Sidorenko, V.F.
Abstract: The results of simulation in the scale models of buildings allowed determining how the air flow speed and direction changes within the street space with various build-up patterns. It was found out that planning conditions cause formation of reverse circulation zones in street canyons due to stationary vortices and, consequently, a high air pollution with the exhaust from motor vehicles. Guidelines are provided for ensuring proper ventilation conditions within urban street space and for preventing dangerous air pollution taking into account closed air circulation.